IMPLEMENTASI KONSEP-KONSEP GEOGRAFI PADA BUKU AJAR GEOGRAFI SMA KELAS X TERBITAN WANGSA JATRA LESTARI - Feby Arinda; Ahyuni Ahyuni (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
This study was written to analyze implementation concept of geography in Wangsa Jatra Lestari geography textbook class X. This research used quantitative method with content analyze approach. The data analyze used percentage technique. The result showed that there were 336 paragraph and 169 questions on Kd 3.2, KD 3.3 and KD 3.4. Implementastion concept of geography is 44% of the 336 paragraphs wich contain general concepts of geography in the form of morphological concepts, utility values, and distance. As many as 19% of the 169 questions that implemented geography and dominant concepts were included in the Taksonomi Bloom classification category in the cognitive domain of C4 or 12 questions (38%). So it can be concluded that the geography textbook class x semsetr 1 still classified as low in implementation concept geography.